Comparative prospective study on the clinical utility of G‐banding and next‐generation sequencing for chromosomal analysis of products of conception under Advanced Medical Care A in Japan - Hidemine Honda; Tsuyoshi Takiuchi; Mika Handa; Nao Wakui; Saori Tsuji; Takeshi Goto; Shota Suzuki; Fumie Saji; Tatsuya Miyake; Sakae Goto; Satomi Okamura; Tomomi Yamada; et al. (Reproductive Medicine and Biology)
Abstract Purpose To compare the clinical utility of G‐banding and next‐generation sequencing (NGS) for chromosomal analysis of products of conception (POC), a crucial tool for detecting fetal chromosomal abnormalities which are major causes of miscarriage and stillbirth. Methods We evaluated the clinical utility of both techniques in a prospective analysis of 40 patients who experienced miscarriages or stillbirths between 6 and 36 weeks of gestation under Advanced Medical Care A in Japan. Both methods were applied to the same POC samples. The primary outcome was the proportion of patients with a presumed cause of miscarriage or stillbirth among all submitted samples. Results NGS presumed the cause in 75.0% (30/40) of cases, significantly outperforming G‐banding's 42.5% (17/40) (p < 0.01). G‐banding could analyze 67.5% (27/40) of the samples owing to culture failure, whereas NGS successfully analyzed all samples (100%, 40/40) (p < 0.01). Among the successfully analyzed samples, NGS presumed the cause in 70.3% (19/27) of cases, compared with 62.9% (17/27) for G‐banding (p = 0.31). For miscarriages before 12 weeks, NGS presumed the cause in 73.5% (25/34) of cases, significantly higher than the 44.1% (15/34) (p < 0.01) presumed using G‐banding. Conclusions These results highlight the superior efficacy of NGS over G‐banding for presuming causes of miscarriage or stillbirth.